balance the given equation HNO3 + I2 -> HIO3+NO2

Asked by priyanshi shrivastava | 11th Dec, 2012, 09:34: PM

Expert Answer:

Using half-reactions:

I2 --> 2HIO3 
1(I2) + 6(H2O) = 2(HIO3) + 10(H+) + 10(e-)
 
HNO3 ----> NO2
1(HNO3) + 1(e-) + 1(H+) = 1(NO2) + 1(H2O)

Multiplying the second half reaction by 10 (to cancel out the electrons) yields,

I+ 10HNO= 2HIO3 + 10NO2 + 4H2O

Answered by  | 12th Dec, 2012, 10:52: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.